Development of Flipbook Based Learning Media to Enhance Elementary Students’ Reading Interest and Learning Outcomes - Fitrianti, Novia; Astuti, Tri (Jurnal Paedagogy, 2026)
This study aims to develop Flisco, a Flipbook Scan Code literacy-based learning medium themed around family and community traditions for third-grade elementary school students, and to evaluate its feasibility and effectiveness in improving students’ literacy interest and learning outcomes. This study employed a mixed-methods approach combining qualitative and quantitative methods within a Research and Development (R&D) framework consisting of eight systematic development stages, with a focus on expert validation and field testing. The study was conducted at SDN Sidomulyo 1 involving 30 students selected through saturated sampling, while 15 students from SDN Sidomulyo 3 participated in a small-scale trial selected through purposive sampling. Data were collected through pretest and posttest assessments as testing techniques, and through observations, interviews, Likert-scale questionnaires, and documentation as non-testing techniques. The validity of the test instruments was established using the Pearson correlation method on 30 items at a significance level of α = 0.05. Data analysis involved normality testing, homogeneity testing, paired-samples t-test, and N-Gain analysis. The validation results from material and media experts indicated that Flisco was categorized as “highly feasible,” with scores of 96% and 94%, respectively. The paired-samples t-test showed a correlation coefficient of 0.787 with a significance value of p < 0.001, confirming that Flisco significantly improved students’ IPAS learning outcomes. The N-Gain score of 76.15% was categorized as high. Furthermore, literacy interest measurements showed that 76.7% of students achieved the very high category, while 23.3% were categorized as high. These findings demonstrate that Flisco is a valid, feasible, and effective literacy-based learning medium that provides an innovative alternative for enhancing elementary school learning experiences.